Pore Extractor 2D: An ImageJ toolkit for quantifying cortical pore morphometry on histological bone images, with application to intraskeletal and regional patterning. Issue 3 (14th September 2022) - Cole, Mary E.; Stout, Sam D.; Dominguez, Victoria M.; Agnew, Amanda M.
Abstract: Objectives: Cortical porosity is used as a proxy of bone quality, fragility, and remodeling activity in anthropological contexts. Histological quantification is limited by time‐intensive manual annotation. Pore Extractor 2D is an ImageJ toolkit developed for computer‐assisted pore identification and automated pore morphometry. Materials and Methods: Toolkit components include: (1) Utilities for cortical border clearing, (2) Image Pre‐Processing: Image contrast enhancement and noise reduction, (3) Pore Extractor: User‐directed options for segmenting, closing, and smoothing pore spaces, (4) Pore Modifier: Utilities to expedite manual correction of extracted pore spaces, and (5) Pore Analyzer: Morphometric analyses by pore type and anatomical region. Pore Extractor 2D was validated against manual annotation in a sample of midshaft mid‐thoracic human ribs ( n  = 30). Intraskeletal and regional analyses were piloted on matched ( n  = 9) human midshaft femora, tibiae, and sixth ribs. Results: Pore Extractor 2D was statistically consistent with manual annotation of bone area, percent porosity, pore density, and mean pore size. The toolkit significantly ( p  < .05) reduced the smoothing effect of manual annotation by fitting pore borders to pixel brightness variations. Intraskeletal analyses found that the femur and tibia significantly exceeded the rib in "cortical" type porosity, while the rib predominantly formed "trabecularized" type porosity. Regional analyses determined that pore system expansion was elevated in the anterior femur, the anterior and medial tibia, and the cutaneous cortex of the rib. Discussion: This toolkit provides expedited, semi‐automated porosity quantification that replicates manual annotation. Intraskeletal and regional variation in pore morphometry reflect localized strain patterning. Abstract : Regional subdivision of semi‐automatically extracted cortical pores is displayed on a histological cross‐section of a human tibia.